Drinking Water Temperature around the Globe: Understanding, Policies, Challenges and Opportunities - Agudelo-Vera, Claudia; Avvedimento, Stefania; Boxall, Joby; Creaco, Enrico; de Kater, Henk; Di Nardo, Armando; Djukic, Aleksandar; Douterelo, Isabel; Fish, Katherine E.; Iglesias Rey, Pedro L.; Jacimovic, Nenad; Jacobs, Heinz E.; et al. (Water (Basel), 2020)
Water temperature is often monitored at water sources and treatment works; however, there is limited monitoring of the water temperature in the drinking water distribution system (DWDS), despite a known impact on physical, chemical and microbial reactions which impact water quality. A key parameter influencing drinking water temperature is soil temperature, which is influenced by the urban heat island effects. This paper provides critique and comprehensive summary of the current knowledge, policies and challenges regarding drinking water temperature research and presents the findings from a survey of international stakeholders. Knowledge gaps as well as challenges and opportunities for monitoring and research are identified. The conclusion of the study is that temperature in the DWDS is an emerging concern in various countries regardless of the water source and treatment, climate conditions, or network characteristics such as topology, pipe material or diameter. More research is needed, especially to determine (i) the effect of higher temperatures, (ii) a legislative limit on temperature and (iii) measures to comply with this limit.